LOOP an eco-friendly and refillable packaging for an alternative and more sustainable "tingi-tingi" purchase of a shampoo - Cutaran, Abigail Danti (College of Fine Arts, University of the Philippines Diliman, 2017)
The Philippines is one of the countries that is known to developing a sachet economy. It is good since it reaches out to the lower bracket income families but at the same time bad since it produces a lot of waste ending in the landfills and other environmental premises. One of the sachet goods that most Filipinos commonly buy are shampoos and shampoo in sachets' are good for one time use only. With further production and use of shampoo sachet of Filipinos the more it would collect waste ending in landfills and oceans. This thesis solve a way on how shampoos could be sold in small quantity scale a.k.a "tingi-tingi" without the use of sachet. LOOP is designed to use eco-friendly, recycled, and refillable packaging along with a refilling system. It is an alternative solution to reach out to the masses of selling small quantity scale a.k.a "tingi tingi" shampoo and at the same time establish an attitude of reuse and recycle to its consumers.